2012
DOI: 10.1111/j.1471-0528.2011.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for recurrent epithelial ovarian cancer: a multi‐institutional study

Abstract: Objective To assess the efficacy and morbidity and mortality of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in recurrent epithelial ovarian cancer (EOC).Design A retrospective study conducted using information extracted from a multi-institutional prospective database on peritoneal surface malignancies (PSMs). Setting Four Italian centres specializing in locoregional treatment of PSM.Population Patients with recurrent EOC.Methods Fifty-six patients underwent 57 combined pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 62 publications
2
47
0
2
Order By: Relevance
“…The study identified a significantly higher 2-and 5-year OS rate in those with HIPEC+CRS+chemotherapy Interestingly, two large studies in this review did not find a statistically significant difference in overall survival between platinum-sensitive and platinum-resistant patients treated with HIPEC+CRS [37,68]. This is an unexpected finding as patients with platinumresistant recurrent EOC often have a far worse prognosis compared to those with platinumsensitive disease when treated with systemic chemotherapy.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
See 3 more Smart Citations
“…The study identified a significantly higher 2-and 5-year OS rate in those with HIPEC+CRS+chemotherapy Interestingly, two large studies in this review did not find a statistically significant difference in overall survival between platinum-sensitive and platinum-resistant patients treated with HIPEC+CRS [37,68]. This is an unexpected finding as patients with platinumresistant recurrent EOC often have a far worse prognosis compared to those with platinumsensitive disease when treated with systemic chemotherapy.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…Similarly, another large study found platinum-resistant interval did not influence the median overall survival or DFS [37]. The OS curves of the two groups (sensitive and resistant) revealed very similar, superimposable patterns in the first 2 years.…”
Section: Platinum Resistancementioning
confidence: 75%
See 2 more Smart Citations
“…In the largest multicenter study, 76 with N = 474 patients, cisplatin was the most commonly used agent (75%) either on its own or in combination with mitomycin or doxorubicin. Five studies 77Y81 used cisplatin with doxorubicin, 77,79,80 paclitaxel, 78 or mitomycin. 79Y81 Three studies used oxaliplatin, 56,72,73 with only 1 study electing to use it in combination (with irinotecan in some patients).…”
Section: Choice Of Hipec Drugs/regimenmentioning
confidence: 99%